Ecological Da'wah Communication: A Case Study of “Project B Indonesia” Waste Bank - Chandra, Afner Gus; Putra, Nursaka (Jurnal Ilmiah Syi'ar, 2024)
Da'wah is essentially aimed at transforming religious values in the form of behavior, translating the language of revelation into concrete actions and integrating the will of God into the demands of reality. In reality, ecological problems should be a concern for all parties, one of the indications is environmental damage which is increasingly worrying and threatening the health and sustainability of humans to live healthy on earth. Under these conditions, it takes the ability of ecological missionary communication to deliver environmental messages to the wider community, one of the institutions that has carried out these activities is Project B Indonesia. This research uses descriptive qualitative research which includes information on the main phenomena which are then explored in the study. Data collection techniques in this study are using interviews, observation and documentation. The data analysis technique used is data reduction, then display the data model, and to find conclusions. The results of this study see that Project B Indonesia has a significant role in tackling the problem of waste, where the ecological missionary communication process is designed with good planning, starting from the formation of communicators who are required to read the Qur'an, determine targets and needs of the audience, compile messages communication that is able to be received by all members of the community, planning appropriate media and channels according to the audience's catch, and setting communication objectives that involve the entire Project B Indonesia team. The application of ecological missionary communication carried out by Project B Indonesia also has varying degrees of success.